Analyses Using National Survey Data From Cameroon, Haiti, and Ghana Indicate the Potential for Bouillon Fortification to Help Fill Dietary Gaps for 5 Nutrients. (7th June 2021) - Engle-Stone, Reina; Adams, Katherine; Kumordzie, Sika; Luo, Hanqi; Wessells, K. Ryan; Adu-Afarwuah, Seth; Ndjebayi, Alex; Teta, Ismael; Régis, Yves-Laurent; Haskell, Marjorie; Vosti, Stephen
Abstract: Objectives: We modeled the potential impacts of bouillon fortification with different levels of vitamin A, folic acid, vitamin B12, iron, and zinc on dietary micronutrient adequacy to inform multi-stakeholder discussions around bouillon fortification programs. Methods: We used individual dietary intake data in Cameroon from women of reproductive age (WRA) and children 1–5 y (n = 902 and 872), and household (HH) survey data in Cameroon (n = 11, 384 HH), Ghana (n = 11, 870 HH), and Haiti (n = 4, 951 HH) to estimate micronutrient (MN) intake. The Adult Male Equivalent method was applied to estimate "apparent intake" of WRA, children, and men from HH surveys. We examined intake of bouillon and calculated prevalence of inadequate (below the estimated average requirement) and high (above the tolerable upper intake level, UL) micronutrient intake. Analyses included the contributions of mandatory fortification of oil or wheat flour at estimated current micronutrient levels. We simulated the impacts of bouillon fortification with varying levels of vitamin A, folic acid, vitamin B12, iron, and zinc on inadequate and high intakes of each nutrient. Results: Bouillon was commonly consumed in all countries, with any reported consumption ranging from 67–81% in Ghana to over 90% in Cameroon and Haiti. Median (apparent) bouillon consumption ranged from 1.6–2.1 g/d for women, 0.7–1.0 g/d for children, and 1.8–2.2 g/d for men. Bouillon fortification with vitamins was predicted to reduce dietary inadequacy (120 μg/g vitamin A: 15–33 percentage points, pp, depending on the country and target group; 80 μg/g folate: 11–33 pp; 1.2 μg/g B12: 12–67 pp) with minimal risk of high intake. In contrast, predicted effects on dietary iron inadequacy were modest (5–12 pp reduction at 5 mg iron/g, assuming 2% absorption). Simulated zinc fortification showed reductions in inadequate absorbable zinc intake (14–42 pp at 3 mg/g), but children's intakes commonly exceeded the UL. Conclusions: Modeling suggests that bouillon fortification could reduce inadequate MN intakes in these countries. Further work is needed to identify fortification levels that will meet criteria for nutritional benefits, technical feasibility, and cost-effectiveness. Funding Sources: This analysis was supported by a grant to UC Davis from Helen Keller International.